2022
DOI: 10.1002/anie.202203016
|View full text |Cite
|
Sign up to set email alerts
|

Modular Introduction of endo‐Binding Sites in a Macrocyclic Cavity towards Selective Recognition of Neutral Azacycles

Abstract: Macrocycles with a functionalized interior, which is a general cavity feature of bioreceptors, are relatively hard to synthesize. Here we report a modular strategy to customize diverse endo-binding sites in the macrocycle cavity. Only two steps are needed. First, one V-shaped functional module bearing an embedded binding site and two 2,5-dimethoxyphenyls as reaction modules are connected. Then the condensation of the resulting monomer and paraformaldehyde directly produces the designed macrocycle. V-shaped mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…7). [31][32][33][34] Interestingly, they found that the macrocyclization process could be modulated by changing the geometrical configurations of these monomers. Linear monomers tended to yield cyclic trimers and pentamers while V-shaped monomers produced cyclic dimers.…”
Section: Chuan-feng Chenmentioning
confidence: 99%
“…7). [31][32][33][34] Interestingly, they found that the macrocyclization process could be modulated by changing the geometrical configurations of these monomers. Linear monomers tended to yield cyclic trimers and pentamers while V-shaped monomers produced cyclic dimers.…”
Section: Chuan-feng Chenmentioning
confidence: 99%
“…Inspired by the synthetic strategies of P­[ n ]­s, researchers have synthesized new macrocycles from the reaction of different alkoxy-substituted aromatic monomers and paraformaldehyde. This led to the rapid discovery of series of macrocycles, including biphenyl­[ n ]­arenes, prism­[ n ]­arenes, rhombicarene, pagoda­[ n ]­arenes, saucer­[ n ]­arenes, leggero pillar[5]­arenes, octopus[3]­arenes, acridane­[ n ]­arenes, methylene-bridged naphthotubes, and others, over the last five years. In addition, the modification at phenylene sites, , methylene bridge, , or upper/lower rims , of P­[ n ]­s resulted in pillar­[ n ]­arene­[ m ]­quinones, tiara­[ n ]­arenes, and others. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, our research group reported a series of novel supramolecular macrocycles, namely biphen[n]arenes and their extended analogues, which were constructed through the Friedel-Crafts alkylation reactions of oligophenyl monomers containing methoxy groups. [25][26][27][28][29][30] On account of this modular synthetic strategy, these macrocycles possess easily adjustable cavity sizes and readily introducible functional groups. In this study, we present the synthesis of a terphen [3]arene functionalised with sulfate groups, which has good water solubility and biocompatibility.…”
mentioning
confidence: 99%